The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1001/jamanetworkopen.2022.30509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Digital Medication Event Reminder and Monitor-Observed Therapy vs Standard Directly Observed Therapy on Health-Related Quality of Life and Catastrophic Costs in Patients With Tuberculosis

Abstract: IMPORTANCELittle is known about whether digital adherence technologies are economical for patients with tuberculosis (TB) in resource-constrained settings.OBJECTIVE To test the hypothesis that for patients with TB, a digital medication event reminder monitor (MERM)-observed therapy provides higher health-related quality of life (HRQoL) and lower catastrophic costs compared with standard directly observed therapy (DOT). DESIGN, SETTING, AND PARTICIPANTSThis study was a secondary analysis of a randomized, 2-arm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The risk of bias for assessments in cross-sectional studies is summarized in Table 2 . The risk of bias assessment for randomized controlled trials showed that six domains were low risk for bias in one study [ 15 ] and each three domains were also low risk for bias in two studies [ 16 , 17 ]. The rest of the domains was either high risk or unclear for bias.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of bias for assessments in cross-sectional studies is summarized in Table 2 . The risk of bias assessment for randomized controlled trials showed that six domains were low risk for bias in one study [ 15 ] and each three domains were also low risk for bias in two studies [ 16 , 17 ]. The rest of the domains was either high risk or unclear for bias.…”
Section: Resultsmentioning
confidence: 99%
“… The total cost per patient diagnosed was higher for women, rural residents; those who received government food for work support, patients with smear-negative pulmonary tuberculosis, and patients who were not screened for TB in at least one district diagnostic center. Tsegahun, 2022 ( 15 ) Open label RCT. Adults aged 18 years or older with new or previously treated, bacteriologically confirmed, and drug-sensitive pulmonary TB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding a social protection component to the TB treatment may improve the treatment outcomes [28] . In addition, implementing a digital medication event reminder may prevent loss to follow-up [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inequalities in infrastructure and access to the internet and electricity are among the major challenges in the implementation and scale-up of DHIs in resource-limited settings. Digital health technologies were recommended to help patients adhere to their treatment; however, for optimal implementation of such technologies, trials evaluating the effectiveness of remote treatment are critically needed (19,(27)(28)(29).…”
Section: Challenges and Limitations To Implementing Digital Health Te...mentioning
confidence: 99%